OP0196 Changing patterns of juvenile idiopathic arthritis patients treated with etanercept from 2000 to 2016 in the german biker registry population. (15th June 2017) - Horneff, G; Minden, K; Foeldvari, I; Ganser, G; Haas, JP; Brunner, J; Becker, I; ,
Abstract : Background: There is increasing experience with Etanercept (ETA) in juvenile idiopathic arthritis in the BIKER Registry. Objectives: To report on practice changes ETA utilization and outcome over a period of 16 years. Methods: 6 cohorts of pts were created according to inclusion period. Patients' and disease characteristics, the utilization of DMARDs, steroids, NSAIDs were analysed. Efficacy was judged by PedACR30/50/70/90, JADAS and ACR-remission. Results: Records from 2105 JIA pts treated with etanercept with at least a baseline and one follow up form were analysed. Most pts were females (67%). The median age of disease onset increased from 5.9 years in the early to 9.3 years in the later cohorts while age at start of treatment remained stable (about 13 years). Median disease duration markedly decreased from 5.3 to about 2 years. Most pts had RF neg. polyJIA followed by extended oligoarthritis. In the more recent cohorts the rate of enthesitis related arthritis increased and the rate f systemic JIA decreased (table). At registry start, 20% of newly enrolled pts belonged to the systemic JIA category compared to <1% in 2016. During the study period, the overall utilization of glucocorticoids at baseline decreased from 54% to 19% (P<0.0001), NSAID from 90% to 72% (P<0.0001), MTX from 78% to 64% (P=0.004). ACR30/50%70/90 response rates at month 12 were 80%/74%/59%/40% and did not vary over time while the rate of patients reaching no active joint/CHAQ DI=0/JADAS-MDA/JADAS-Remission/ACR-Remission increased from 43%/35%/44%/19%/41% to 69%/48%/45%/26%/63%. Conclusions: In recent years, children have been treated earlier, received less concomitant treatment with NSAIDS, corticosteroids as well as DMARDs. More recent cohort of patients had less severe disease at baseline, but also showed a markedly better outcome already at one year of treatment reflected by higher rates of patients with no active joint, a CHAQ DI of 0, a JADAS-MDA, and ACR-Remission. These data suggest that early disease control and better pre-selection of patients who need biologics are important to improve outcome and safety in children with JIA. Disclosure of Interest: G. Horneff Speakers bureau: Abbvie, Pfizer, Roche, Novartis, MSD, K. Minden Speakers bureau: Abbvie, Pfizer, Roche, Genzyme, Pharm-Allergan, I. Foeldvari: None declared, G. Ganser: None declared, J. Haas: None declared, J. Brunner: None declared, I. Becker: None declared